Representación del personaje sexodiverso en la dramaturgia mexicana - Rivera, Octavio; Guerra, Humberto (Latin American Theatre Review, 2010)
This is an analysis of the representation of the gay-lesbian theme, as well as theportrayal of non-heteronormative characters (including lesbians, homosexuals and gays) inMexican dramatic literature. The article examines various publications, including a text from theeighteenth century, another from the nineteenth century, and various representative selectionsof dramaturgy from the twentieth century. These selected texts of Mexican dramaturgy offer awide variety of representations of “sexodivirsity,” which sometimes affirm stereotypes and atother times offer new representations of sexual identity. In the latter group, that of new sexualrepresentations, sexual identity sometimes seems to lose its importance or its efficiency as anidentifying sign, while in other texts it recovers the status of the core dramatic element. (ORand HG, Article in Spanish)